Psychiatric comorbidity in patients with migraine: A standardized interview-based study - Preeti Sharma; Santosh Kumar; Vidhata Dixit; Chandra Shekhar Sharma; Suprakash Chaudhury (Industrial Psychiatry Journal)
Background: Comorbidity of various psychiatric conditions with migraine is common and important. A thorough analysis of mental conditions in migraine is essential to encourage the holistic care of such patients. Aim: To assess psychiatric comorbidity in patients with migraine using a well-standardized clinical diagnostic tool. Methods: This cross-sectional study was conducted in the outpatient department of a tertiary care hospital in North India. Persons with migraine attending the facility were enrolled as per the inclusion and exclusion criteria set for this study. The ICD-10 mental disorder symptom checklist was the principal tool to assess the psychiatric comorbidity in the patients. Results: Total Patients recruited were 146 out of which 70.5% had a psychiatric comorbidity. Depressive disorder (17.1%) was the most common while delusional disorder (4.1%) was the least common psychiatric disorder comorbid with migraine. Other comorbid psychiatric diagnoses were recurrent depressive episodes (6.8%), dysthymia (10.3%), bipolar affective disorder (7.5%), panic disorder (5.5%), generalized anxiety disorder (8.2%), mixed and other anxiety disorders (6.2%), obsessive-compulsive disorder (6.2%), post-traumatic stress disorder (4.8%), adjustment disorders (5.5%), dissociative (conversion) disorders (6.8%), and somatoform disorders (6.2%). Lower socioeconomic status and the presence of aura with migraine are two important patient-related factors linked with the occurrence of any psychiatric comorbidity in migraine. Conclusion: The prevalence of comorbid psychiatric disorders in migraine patients is very high. The relationship between demographic and medical information of people with migraine with individual psychiatric comorbidities is complex.